THE INFLUENCE OF TEACHERS’ PROFESSIONAL COMPETENCE TO CARRY OUT THE PROCESS OF LEARNING IN KINDERGARTEN THOURGHOUT SUBDISTRICT TAMPAN OF PEKANBARU CITY - Nur Cahaya Nur Cahaya; Wusono Indarto Wusono Indarto; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The purpose of this study was to determine how much influence the professional competence to carry out the process of learning in kindergarten throughtout subdistrict tampan of pekanbaru city.This research isquantitativeusingcorrelationaltechniques. Based on theresults ofthe percentage ofthe professionalcompetenceof teachersinkindergartenSubdistrict Tampanof Pekanbaru Citywas moderatewitha percentageof 87.5%. based on apercentage ofthe implementationprocess oflearninginkindergartensubdistrict Tampan of Pekanbaru Cityclassified as moderatebythe percentage of78.86%. And based onthe results ofthe linearregressionthere are positive influencebetweenthe professionalcompetenceof teachersonthe implementation ofthe learningprocessinkindergartenSubdistrict Tampan of Pekanbaru Cityby65.5%. While the remaining35.5% is influencedbyotherfactorsthatditidakexamined in this study. So itcanbe concludedthat there are significantprofessionalcompetenceof teacherstowardsthe implementation ofthe learningprocessinkindergartenSubdistrict Tampan of the city of Pekanbaru. Key word: Competence Professionalof Teachers’, the Process of Learning